2017
DOI: 10.1007/s10291-017-0674-x
|View full text |Cite
|
Sign up to set email alerts
|

On the combined effect of periodic signals and colored noise on velocity uncertainties

Abstract: of seasonal signals becomes less important, and the powerlaw character of the residuals starts to play a crucial role in the determined velocity uncertainties. With reference frame and sea level applications in mind, we argue that 7 and 9 years of continuous observations is the threshold for white and flicker noise, respectively, while 17 years are required for random-walk to decrease GDP below 5% and to omit periodic oscillations in the GNSS-derived time series taking only the noise model into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 64 publications
0
34
0
1
Order By: Relevance
“…After the common annual seasonal curve was modelled with MSSA and removed from the GPS position time series, the residual station-specific annual curve was removed with LSE, as it may affect the character of stochastic part of the GPS data Bogusz and Klos 2016;Klos et al 2018b). We showed that the amplitudes of residual oscillations do not exceed 2 mm at maximum.…”
Section: Discussionmentioning
confidence: 92%
“…After the common annual seasonal curve was modelled with MSSA and removed from the GPS position time series, the residual station-specific annual curve was removed with LSE, as it may affect the character of stochastic part of the GPS data Bogusz and Klos 2016;Klos et al 2018b). We showed that the amplitudes of residual oscillations do not exceed 2 mm at maximum.…”
Section: Discussionmentioning
confidence: 92%
“…As was previously shown, the assumption on white-noise-only leads to an underestimation of velocity uncertainty of several times [32,54], as the covariance matrix of observations is created based on the amplitude of white-noise-only a and the identity matrix I, as in:…”
Section: Methodsmentioning
confidence: 99%
“…Bos et al [31] considered this problem further and proved that adding a white plus power-law noise model causes the accuracy of the linear trend to decrease. Recently, Klos et al [32] demonstrated that this decrease is directly related to the type of power-law noise added, which can be nicely summarized that any of the time series components which have been un-or mis-modelled will influence the value of velocity along with its uncertainty.…”
Section: Introductionmentioning
confidence: 98%
“…The Crustal Movement Observation Network of China (CMONOC) is an important scientific infrastructure in China, which initially contained 27 Continuous Global Positioning System (GPS) stations in 1999 and then was extended to 260 GPS stations since 2011. CMONOC has provided useful datasets to facilitate the investigations of various geophysical phenomena, such as global plate motion [1], regional tectonic deformation [2], uplift of the Tibetan Plateau [3], land subsidence of Furthermore, periodic signals contribute to the temporal noise in GPS position time series [35,36] and both of them can be affected by CMC filtering. Therefore, CMC filtering has a further effect on velocity estimates and their uncertainties.…”
Section: Introductionmentioning
confidence: 99%